Acoustic Measurements and Simulations on Yachts: An Evaluation of Airborne Sound Insulation - Michele Rocca; Francesca Di Puccio; Paola Forte; Francesco Fidecaro; Francesco Artuso; Simon Kanka; Francesco Leccese (Journal of Marine Science and Engineering)
The perceived acoustic comfort on board modern yachts has recently been the subject of specific attention by the most important classification societies, which have issued new guidelines and regulations for the evaluation of noise and vibrations. The evaluation of the acoustic insulation performance of the internal partitions of yachts is, therefore, a very current topic. The estimation of the acoustic performance of internal partitions can be very complex; on the one hand, on-board measurements can be extremely difficult, but on the other hand, manual or software calculation is extremely complex or potentially affected by non-negligible errors, which is also due to the high amount of highly detailed information required. This paper explores the possibility of using simplified models, commonly used in building construction, to determine the acoustic insulation of the internal partitions of yachts in the design phase, without having to resort, even from the beginning, to very advanced calculation tools such as those based on the Finite Elements Method or Statistical Energy Analysis. Using a 44 m yacht as a case study, this paper presents the results of a series of acoustic simulations of single partitions and compares them with the results of an on-board measurement campaign. From the comparison of the obtained results, it was possible to state that the simulations of single partitions (therefore, those not of the whole vessel) can be useful in the design phase to verify compliance with the acoustic requirements requested by the classification societies. Considering that the propagation of sound and vibrations through the structures is a determining factor for the correct acoustic design of the vessel and therefore for the achievement of adequate levels of acoustic comfort, the analysis with simplified models (which consider the single partition) can be extremely useful in the preliminary phase of the design process. Subsequently, starting from the data acquired in the first simulation phase, it is possible to proceed with more complex simulations of specific situations and of the whole vessel.